In vitro Antimicrobial activity and GCMS Analysis of Anethum graveolens L. - Punam Joshi; Manoj Gahlot; Harish Chandra (Environment Conservation Journal, 2010)
Plant-based medicine has served mankind for centuries and an impressive number of modern drugs have been isolated from natural sources. The last 20–25 years have witnessed renewed interest in folkloric remedies to fight microbial diseases owing to the emergence of multidrug resistant microorganisms. In present study seed oil of Anethum graveolens was investigated against 11 bacterial strains and found that the extract was active against all tested bacterial species.